2003
DOI: 10.1034/j.1601-0825.2003.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tongue lesions in Hungarian children

Abstract: In some cases early recognition of tongue lesions may provide useful diagnostic markers for some diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
6
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 18 publications
3
59
6
4
Order By: Relevance
“…While our results demconsistent. While our results demWhile our results demonstrate higher prevalence among females, which was also the finding in Thailand (16), others reported higher prevalence among male children in Hungary (17). On the other hand, other studies found no gender differenc- Approximately 28% of those with geographic tongue reported symptoms, where the majority of them (63%) had soreness with acidic food and drink.…”
Section: Discussioncontrasting
confidence: 53%
“…While our results demconsistent. While our results demWhile our results demonstrate higher prevalence among females, which was also the finding in Thailand (16), others reported higher prevalence among male children in Hungary (17). On the other hand, other studies found no gender differenc- Approximately 28% of those with geographic tongue reported symptoms, where the majority of them (63%) had soreness with acidic food and drink.…”
Section: Discussioncontrasting
confidence: 53%
“…The prevalence of altered frenulum for this study was 0.8%, consistent with another result presented in the literature, in which the prevalence was 0.88% (19) . The results of the present study differ from those found in another study (20) , in which the prevalence was 22.54%.…”
Section: Discussionsupporting
confidence: 81%
“…Não há consenso nos critérios utilizados para a avaliação e classificação anatômica do frênulo da língua, o que pode justificar a grande variação, entre 0,88% e 12,7%, nos índices de incidência (SEDANO et al, 1989;BALLARD;AUER;KHOURY, 2002;PEREIRA et al, 2002;MARCHESAN, 2003MARCHESAN, , 2005MARCHESAN, , 2010VÖRÖS-BALOG;VINCZE;BÁNÓCZY, 2003;BRAGA et al, 2009). Na literatura consultada, apenas um protocolo foi proposto para avaliação do frênulo lingual em bebês até seis meses de idade (HAZELBAKER, 1993).…”
Section: Introductionunclassified